A proteção dos credores sociais por meio das demonstrações financeiras: um retorno às bases que garantem a responsabilidade limitada - Ribas, Roberta de Oliveira e Corvo (2016)
This paper aims to demonstrate that the protection of creditors of the legal entity that grants limited liability to its shareholder shall focus on controlling the use and disposal of assets of the legal entity itself. The study of grounds of civil liability in Brazilian Law together with the principle of assets autonomy of the legal entity and the purpose of limited liability confirm that the national law does not admit to relativize the rule of limited liability, except in cases of fraud and abuse of the legal entity. Given this limitation, resulting from a systematic analysis of the Brazilian Law, and in order to offer a proposition of fair coexistence between the interests of creditors and encouragement of free enterprise provided by limited liability, which is a constitutional command, it proves the importance of the mechanisms of control of assets of the corporation through its financial statements. In this sense, if assets and rights of a legal entity are intended to fulfill a specific purpose, it is for the Law to provide suitable tool to ensure that the risks inherent in the developed activity are covered exclusively by these assets and rights. This tool is accounting, which through the financial statements it produces, it records and controls assets of the entity, providing conditions for decision-making. Its proper use can (and should) prevent intrinsic adversities of any activity subject to risks. The purpose is to resume the mechanism that allows the existence of limited liability, since this doctrine/established principle is not intended to curtail the guarantee of creditors, but rather to encourage those who seek to produce and circulate assets and services to society through the organized economic activity